The impact of oral health on the quality of life in patients with CKD prior to renal transplantation: A pilot study - Maciel, Aloizio Premoli; Manoel, Murilo de Almeida; Rubira, Cássia Maria Fischer; Bueloni, Tricya Nunes Vieira; Santos, Paulo Sérgio da Silva (Brazilian Journal of Transplantation, 2016)
Introduction: Renal transplantation is an important modality of renal replacement therapy for patients with chronic kidney disease in advanced stages. Unlike oral diseases as foci of infection, chronic inflammation and other factors are directly linked to a successful transplant. The purpose of this research is to assess the impact of oral health on the quality of life of CKD-bearer individuals in the pre-transplantation period. Methods: It was assessed 25 individuals in kidney transplantation schedule in relation to oral alterations, mechanically stimulated sialometry (MSS) and nonstimulated sialometry (NSS), periodontal status by community periodontal index, gingival index, plaque index, and the OHIP-14 quality of life questionnaire was applied. Results: Lip dryness was present in 14 (56%) cases, preceded by coated tongue 10 (40%), fissured tongue 9 (36%), candidiasis 7 (28%), lingual papilla atrophy 4 (16%), pallor of the buccal mucosa 4 (16%) and 2 (8%) cases of acute periodontal abscess. Hyposalivation was observed in 17 (68%) patients who underwent SNE, and in 13 (52%) patients under SME. Most patients have microbial biofilm accumulation inside the periodontal pocket, and moderate gingival inflammation with bleeding under manipulation and edema, with 82% bleeding probing, 88% with dental calculus and 52% with periodontal pocket under probing between 4 and 5 mm depth. In the present sample, 32% of patients had medium impact of oral health on the quality of life. Conclusion: Mouth bacterial and fungal infections were common and may be related to hyposalivation. Those conditions had a negative impact on the quality of life in individuals in kidney transplantation schedule.